Analisis Penerapan Organisasi Pembelajaran pada PT Studio Mineral Batubara (SMB) - Mochtoha, Himawan (Politeknik Negeri Batam, 2024)
This research aims to analyze how PT SMB implements the learning organization framework. A learning organization consists of three pillars; first, an environment that supports learning, second concrete learning processes and practices, and third is leadership that supports learning. This study is designed as an exploratory descriptive research and uses qualitative analysis method. There were two research tools consisting of questionnaires and semi-structured interviews conducted consecutively. The results showed that two of the three pillars scored below the median. The first pillar, environment that supports learning scored 81 above the median score of 71. The second pillar, concrete learning processes and practices scored 68 lower than the median score of 78. The third pillar, leadership that supports learning scored 74 points lower than the median score of 76. The results of the questionnaire data are also supported by data from interviews with PT SMB's top management, so this shows that PT SMB has not fully implemented a learning organization, so PT SMB needs to make improvements and improvisations to the implementation of the learning organization.